Ka-band dual sheet beam traveling wave tube using supported planar ring-bar slow wave structure. Issue 16 (1st November 2020) - Dong, Yang; Chen, Zijun; Li, Xinyi; Wang, Hexin; Wang, Zhanliang; Wang, Shaomeng; Lu, Zhigang; Gong, Huarong; Duan, Zhaoyun; Feng, Jinjun; Gong, Yubin
Abstract : A dual-beam planar slow wave structure (SWS), named dielectric supported ring-bar SWS is proposed in this paper. The planar SWS is supported by two dielectric rods at the side edges, making it fit for dual sheet beam operation. The high frequency and transmission characteristics of the proposed SWS are investigated. The backward-wave oscillation and higher harmonic waves are effectively suppressed by setting two cathodes in the same plane parallel to the SWS and negative phase-velocity jumping. The hot performance of the proposed SWS is carried out by using particle-in-cell (PIC) simulation, in which two sheet electron beams (9.7 kV, 0.2 A) are employed to provide direct current power. With an input power of 1W, the output power is 180 W at 38 GHz and the corresponding gain is 22.6 dB. Besides, after adding dielectric rods to the output part, the entire structure dissipates heat well by thermal analysis.